2015
DOI: 10.1002/ajmg.a.37046
|View full text |Cite
|
Sign up to set email alerts
|

Pure duplication of 19p13.3 in three members of a family with intellectual disability and literature review. Definition of a new microduplication syndrome

Abstract: This paper describes the presence of an interstitial pure duplication of 19p13.3 (4.95 Mb) in a patient with intellectual disability studied by array-CGH which was initially considered as a de novo alteration. The discovery of the same chromosomal alteration in a first-degree cousin of this patient led us to investigate the presence of insertional translocations, which were consequently found in three family generations. The same duplication was found in three intellectually disabled patients and among the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Chromosome 19 abnormalities are very uncommon compared to those found in other chromosomes of the human karyotype [Orellana et al, 2015]. In addition, Y;autosome translocations are infrequent genomic rearrangements that appear in 1/2,000 individuals in the general population and commonly involve an acrocentric chromosome [Wang et al, 2017].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chromosome 19 abnormalities are very uncommon compared to those found in other chromosomes of the human karyotype [Orellana et al, 2015]. In addition, Y;autosome translocations are infrequent genomic rearrangements that appear in 1/2,000 individuals in the general population and commonly involve an acrocentric chromosome [Wang et al, 2017].…”
Section: Discussionmentioning
confidence: 99%
“…2 ; Table 1 ). However, they do not present a typical CFC4 phenotype because they lack other distinctive features, such as thin and curly hair [Siggberg et al, 2010;Nowaczyk et al, Cytogenet Genome Res 2020;160:177-184 DOI: 10.1159/000507561 182 2014; Nevado et al, 2015;Orellana et al, 2015;Novikova et al, 2017].…”
Section: Nonmosaic Trisomy 19pmentioning
confidence: 99%
See 1 more Smart Citation
“…Later on, several independent groups suggested that this new duplication syndrome included a similar SRO at 19p13.3. 6,7 Ubiquitin E3 ligases represent a large family of proteins, which are involved in many cellular pathways by regulating the expression of other proteins through the proteasome. 8 Pathogenic variants in these genes are related to different diseases, including cancer, immune, neurodegenerative and endocrine disorders.…”
Section: Peer Reviewmentioning
confidence: 99%
“…Clinical features include abnormal head circumference in most patients (macrocephaly with the deletions and microcephaly with the duplications), ID with DD, hypotonia, speech delay, abnormality of the esophageal function, abnormalities of the limbs, umbilical hernia and common dysmorphic features. Later on, several independent groups suggested that this new duplication syndrome included a similar SRO at 19p13.3 …”
Section: Introductionmentioning
confidence: 99%